Emergency laparoscopic Hartmann procedure no longer a subspecialist operation: a retrospective cohort study at an Australian non-subspecialized center - Daniel Cattanach; Peter Tilleard; Jana Bednarz; Bree Stephensen (Journal of Minimally Invasive Surgery)
Purpose: An open Hartmann (OH) procedure generally remains the standard of care for several emergent colorectal conditions. There is a perception that the laparoscopic approach is limited to large subspecialist centers. This study aimed to investigate the outcomes of these emergency procedures in a non-subspecialized regional center. Methods : We conducted a retrospective cohort analysis on patients who underwent an emergency Hartmann procedure between 2019 and 2023 within a general surgery unit at a regionally located tertiary-level Australian hospital. Patients were classified as having undergone either OH or laparoscopic Hartmann (LH) procedures. Our primary outcome of interest was length of hospital stay (LOS). Secondary outcomes included time to return of gut function, morbidity, and reversal. Differences between the OH and LH groups were assessed descriptively and using confounder-adjusted regression. Results : We identified 115 patients (83 underwent OH, 32 underwent LH) during the study period. The adjusted estimated mean LOS for patients undergoing an OH procedure was 15.8 days (95% confidence interval [CI], 13.7-17.9) compared to 9.6 days (95% CI, 7.4-11.9) for patients undergoing an LH procedure. The mean time taken for the return of gut function was estimated to be 34% longer following an OH procedure compared to an LH procedure (adjusted incidence rate ratio, 1.34 days; 95% CI, 1.00-1.81). Morbidity was similar between groups. The LH group had higher rates of laparoscopic reversal (91.7% vs. 33.3%). Conclusion : The expected benefits of laparoscopic surgery may extend to the emergency colorectal setting and LH procedures can be performed safely in a non-subspecialized center.